On the issue of the development of criminological science in Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2022)
The article discusses the main directions of development of criminological science in conditions of social instability, and the manifestation of a whole range of destabilizing factors that threaten the national security of Ukraine. These are, first of all, Russian armed aggression against Ukraine, violation of the laws and customs of war, separatism, complete non-compliance with international law, international terrorism, extremism, organized transnational crime and other factors of a destabilizing nature. These elements include the following: expansion of the subject component of criminological science, taking into account the emergence of new social relations that require legal settlement and, accordingly, intensification of the development of individual criminological sub-sectors (theories) on the basis of their selection as a separate subject of study; strengthening the scientific potential as the basis for scientific support for combating crime; expanding the scope of practical application of the results of criminological research; streamlining criminological legislation as the basis for regulatory and legal support for combating crime; use of elements and technologies of artificial intelligence in combating crime.It has been emphasized that the rapid globalization transformations that have been taking place recently led to the reform of almost all spheres of society. Social transformations inevitably affected criminological science. Emphasis has been placed on the exclusive role of criminological science in the study of criminal-illegal behavior of people and the development of measures to combat crime in a crisis state of social development. The need for further comprehensive research in the direction of determining the social role, functions and directions of development of modern criminology has been summed up.The importance of further development of modern criminological science and practical activities to combat crime, which determines the need to introduce the latest innovative approaches to the process of cognition of social phenomena in conditions of social instability, a change in the paradigm of combating crime in order to predict its possible modifications in the future have been argued.
Keywords: criminology; directions of development of criminology; criminological legislation of Ukraine; criminological concept; crime; crime prevention; artificial intelligence.